Stabilized ladle furnace steel slag for glycerol carbonate synthesis via glycerol transesterification reaction with dimethyl carbonate. (1st February 2017) - Okoye, P.U.; Abdullah, A.Z.; Hameed, B.H.
Highlights: Glycerol carbonate (GC) was synthesized utilizing glycerol transesterification pathway. Ladle furnace (LF) steel slag waste catalyzed the glycerol transesterification reaction. Sodium hydroxide stabilizes the LF slag against leaching of active sites. The catalyst can sustain five cycles of reuse without serious deactivation. Abstract: Abundant waste from ladle furnace (LF) steel slag industry was utilized to catalyze the glycerol transesterification reaction with dimethyl carbonate (DMC) to synthesize valuable glycerol carbonate (GC). LF slag was modified using various sodium hydroxide (NaOH) loadings (1–15 wt.%), and the catalyst samples were characterized using XRD, FTIR, TPD-CO2, and EDS techniques. Modifying the LF using different NaOH loadings enhanced the stability, basicity, and basic strength of LF. Favorable reaction conditions at the best glycerol conversion and GC yield were investigated via reaction influencing parameter screening. Thus, the 10 wt.% NaOH incorporated in LF under the reaction conditions of 75 °C, DMC-to-glycerol molar ratio of 2, and 3 wt.% catalyst dosage achieved 99% glycerol conversion and 97% GC yield. The catalyst exhibited sufficient heterogeneity and was utilized in five successive cycles of the experiment without serious deactivation.